Update of the Imine-Anion-Mediated Smiles Rearrangement: Application to Migration of Electron-Neutral/Rich Aromatic Groups - Jinno, Shunki; Kawasaki-Takasuka, Tomoko; Mori, Keiji (Synlett, 2024)
We have revisited the imine-anion-mediated Smiles rearrangement for the synthesis of ortho-hydroxyphenyl arylketimines. Detailed examinations revealed that migration of various aromatic groups, previously considered to be unsuited to SNAr-type reactions, such as electron-rich or sterically hindered aromatic groups, can be accomplished by introducing bulky 9-anthryllithium as a nucleophile. Among the aromatic groups examined, naphthyl groups (1- and 2-naphthyl groups) exhibited an excellent performance, and their migration ability was well illustrated by the reaction with less bulky nucleophiles.
Keywords: imines; Smiles rearrangement; SNAr reaction; nitriles; nucleophilic addition